Clinical Handbook of Emotion-Focused Therapy. 2019
DOI: 10.1037/0000112-007
|View full text |Cite
|
Sign up to set email alerts
|

How clients “change emotion with emotion”: Sequences in emotional processing and their clinical implications.

Abstract: This chapter explores the sequential model of emotional processing proposed by Pascual-Leone and Greenberg (2007). We first present a case illustration and then describe the common emotions and sequences that clients seem to have during productive emotional processing. Next, we review process-to-outcome research conducted on this model of emotional processing, highlighting implications for treatment. Finally, we discuss how the model of change can be translated into a heuristic for practicing therapists. A map… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Pascual-Leone and Greenberg [43] demonstrated that the achievement of the emotional states in the AMM category proceeded in the occurrence of the emotional states present in the EED category. Also, in research using this model in a therapeutic context, the presence of sequential links between various states is demonstrated, regardless of the type of therapeutic modality applied [44,45,48,61]. Complementarily, Welling [47] reflects on the importance of the transformative emotional sequence as a common therapeutic principle of change, reinforcing the idea of the need for a prior activation of a problematic emotional state, followed by the activation of adaptive emotional states.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Pascual-Leone and Greenberg [43] demonstrated that the achievement of the emotional states in the AMM category proceeded in the occurrence of the emotional states present in the EED category. Also, in research using this model in a therapeutic context, the presence of sequential links between various states is demonstrated, regardless of the type of therapeutic modality applied [44,45,48,61]. Complementarily, Welling [47] reflects on the importance of the transformative emotional sequence as a common therapeutic principle of change, reinforcing the idea of the need for a prior activation of a problematic emotional state, followed by the activation of adaptive emotional states.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, the authors presented a "saw-toothed"/zig-zag pattern that jointly described change within and between sessions. Pascual-Leone and Kramer [61] also noted the existence of this pattern when referring to the occurrence of emotional "collapses", where patients, when making initial attempts to move towards primary adaptive emotions, eventually regress to their initial distress expressions. Focusing on this collapse argument, two lines of thought occur to us that could explain this result.…”
Section: Discussionmentioning
confidence: 95%
“…One is assertive or protective anger, which affirms existential needs and protects boundaries. The other is grief at recognizing loss and woundedness, accompanied by a desire to console oneself and reach out to others for emotional connection and support (Pascual-Leone & Kramer, 2019). AEDP, on the other hand, derives its foundation mainly from short-term dynamic therapies, experiential therapies, attachment research, affective neuroscience, and psychology of emotion (Fosha, 2000).…”
Section: Affect-focused Integrative Therapymentioning
confidence: 99%
“…One is assertive or protective anger, which affirms existential needs and protects boundaries. The other is grief at recognizing loss and woundedness, accompanied by a desire to console oneself and reach out to others for emotional connection and support (Pascual‐Leone & Kramer, 2019).…”
Section: Affect‐focused Integrative Therapymentioning
confidence: 99%